Pamaldus pilietis LDK Baroko laidotuvių pamoksluose - Vaitkevičiūtė, Viktorija (Literatūra, 2015)
Reflecting on the Baroque funeral sermons and using the topic of intrinsically precious origin, images of good citizen and warrior of the Christ, the article discloses the contemporary concept of the identity of the citizen of the Grand Duchy of Lithuania. These texts create an image of an ideal noble person, which has no freedom of choice, as by inheriting the nobleness the identity is given for granted. The noble person has to be a brave warrior-knight, fighting for freedom, justice, the homeland and the catholic faith. The character of the funeral sermons perfectly combines a brave warrior and a pious believer. The image of a pious citizen had to affect the feelings of contemporary listeners and readers, to awake the public spirit and to focus on certain ethical norms.